2009
DOI: 10.1088/0957-4484/20/22/225701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rate capability of nanostructured amorphous and anatase TiO2for lithium insertion using anodic TiO2nanotube arrays

Abstract: Nanostructured amorphous and anatase TiO2 are both considered as high rate Li-insertion/extraction electrode materials. To clarify which phase is more desirable for lithium ion batteries with both high power and high density, we compare the electrochemical properties of anatase and amorphous TiO2 by using anodic TiO2 nanotube arrays (ATNTAs) as electrodes. With the same morphological features, the rate capacity of nanostructured amorphous TiO2 is higher than that of nanostructured anatase TiO2 due to the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
148
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 40 publications
13
148
0
Order By: Relevance
“…However, its practical capacity and high-rate capability are limited due to the low Li-ion diffusivity and electronic conductivity during reversible Li-ion insertion/extraction process [4][5][6]. In order to improve the electrochemical performance of TiO 2 materials, nanotechnology has been explored to provide increased reaction active sites and short diffusion lengths for electron and Li-ion transport [7][8][9][10][11][12][13]. In addition, a variety of approaches have also been developed to increase the electronic conductivity of the TiO 2 , such as adding conductive agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, its practical capacity and high-rate capability are limited due to the low Li-ion diffusivity and electronic conductivity during reversible Li-ion insertion/extraction process [4][5][6]. In order to improve the electrochemical performance of TiO 2 materials, nanotechnology has been explored to provide increased reaction active sites and short diffusion lengths for electron and Li-ion transport [7][8][9][10][11][12][13]. In addition, a variety of approaches have also been developed to increase the electronic conductivity of the TiO 2 , such as adding conductive agents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that nanostructured rutile can strongly enhance both the capacity and the rate capability,14, 26 indicating that the nanosized rutile structures could be the promising anode materials. Moreover, it has been shown that the presence of high surface amorphous TiO 2 can enhance the Li ions storage capacities owing to a pseudocapacitance effect 25, 26, 27, 28. Finally, the presence of straight nanochannels is also very favorable for Li ions diffusion 30.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, anatase and rutile phases exist and alternatively appear in the same nanowire frequently, and amorphous is at the surface of the nanowires (Figures 1, S3, Supporting Information). Thus, the formed amorphous/crystalline hybrid nanowires are normally the reason for the very short plateau and the long sloped behavior of discharge processes 9, 26, 27. Due to this special superstructure, it was highly reversible during the following discharge–charge cycles, leading to an excellent capacity retention rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anodizing methods for creating nanofeatured films on titanium substrates have been extensively studied under a variety of similar conditions [61], [87][88][89][90][91][92][93][94]. The varying methods differ in substrate thickness, surface preparation, electrolyte composition, electrolyte concentration, anodizing potential, and anodizing duration.…”
Section: B Background On the Techniquementioning
confidence: 99%